Damage of a large-scale reinforced concrete wall caused by an explosively formed projectile (EFP) - Li-kai Hao; Wen-bin Gu; Ya-dong Zhang; Qi Yuan; Xing-bo Xie; Shao-xin Zou; Zhen Wang; Ming Lu (Defence Technology, 2023)
To quickly break through a reinforced concrete wall and meet the damage range requirements of rescuers entering the building, the combined damage characteristics of the reinforced concrete wall caused by EFP penetration and explosion shock wave were studied. Based on LS-DYNA finite element software and RHT model with modified parameters, a 3D large-scale numerical model was established for simulation analysis, and the rationality of the material model parameters and numerical simulation algorithm were verified. On this basis, the combined damage effect of EFP penetration and explosion shock wave on reinforced concrete wall was studied, the effect of steel bars on the penetration of EFP was highlighted, and the effect of impact positions on the damage of the reinforced concrete wall was also examined. The results reveal that the designed shaped charge can form a crater with a large diameter and high depth on the reinforced concrete wall. The average crater diameter is greater than 67 cm (5.58 times of charge diameter), and crater depth is greater than 22 cm (1.83 times of charge diameter). The failure of the reinforced concrete wall is mainly caused by EFP penetration. When only EFP penetration is considered, the average diameter and depth of the crater are 54.0 cm (4.50 times of charge diameter) and 23.7 cm (1.98 times of charge diameter), respectively. The effect of explosion shock wave on crater depth is not significant, resulting in a slight increase in crater depth. The average crater depth is 24.5 cm (2.04 times of charge diameter) when the explosion shock wave is considered. The effect of explosion shock wave on the crater diameter is obvious, which can aggravate the damage range of the crater, and the effect gradually decreases with the increase of standoff distance. Compared with the results for a plain concrete wall, the crater diameter and crater depth of the reinforced concrete wall are reduced by 5.94% and 9.96%, respectively. Compared to the case in which the steel bar is not hit, when the EFP hit one steel bar and the intersection of two steel bars, the crater diameter decreases by 1.36% and 5.45% respectively, the crater depth decreases by 4.92% and 14.02% respectively. The EFP will be split by steel bar during the penetration process, resulting in an irregular trajectory.